Voicing and register in Ngãi Giao Chrau: Production and perception studies. (January 2022) - Tạ, Thành Tấn; Brunelle, Marc; Nguyễn, Trần Quý
Highlights: Ngãi Giao Chrau has lost its onset voicing contrast and developed a register system. Register cues include phonation type, vowel quality, and pitch differences. Speakers roughly employ the same phonetic properties in perception as in production. No straightforward correlation between production and perception at the individual level. Abstract: Chrau, a South Bahnaric language of the Austroasiatic family spoken in South Vietnam, has been described as having a voicing contrast in onset stops. However, a production experiment reveals that rather than a voicing contrast, Chrau, like many other Austroasiatic languages, has register, a two-way contrast realized on syllables through a bundle of phonetic properties including phonation type, vowel quality, and pitch differences. Stop voicing is marginally present in some speakers but seems to be an optional property of register. The results of a perception study on register further suggest that speakers roughly employ the same phonetic properties in perception as in production. Individual variation is observed in both production and perception, but there is not a straightforward correlation between the two modes at the individual level—an indication that listeners' perception is flexible enough to accommodate variation in production. Our results raise questions about the diachronic scenarios proposed to account for the transphonologization of onset voicing into register and tone in Mainland Southeast Asian languages.